2014
DOI: 10.1007/s11255-014-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

Do blood groups have effect on prognosis of patients undergoing radical cystectomy?

Abstract: ABO blood group and Rh factor were not associated with the prognosis of bladder cancer patients who underwent radical cystectomy. However, prospective studies are needed in larger patient series for further evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In urothelial bladder carcinoma patients after radical cystectomy, the blood type B was associated with a greater likelihood of lymphovascular invasion and positive soft tissue margins, and blood type B patients showed a significantly higher urothelial bladder carcinoma-related mortality than those with the blood types O and AB (48). By other researchers, the ABO blood group was not associated with the prognosis of bladder cancer patients who underwent radical cystectomy (49).…”
Section: Blood Group or (95% Ci)mentioning
confidence: 84%
“…In urothelial bladder carcinoma patients after radical cystectomy, the blood type B was associated with a greater likelihood of lymphovascular invasion and positive soft tissue margins, and blood type B patients showed a significantly higher urothelial bladder carcinoma-related mortality than those with the blood types O and AB (48). By other researchers, the ABO blood group was not associated with the prognosis of bladder cancer patients who underwent radical cystectomy (49).…”
Section: Blood Group or (95% Ci)mentioning
confidence: 84%
“…The sample size varied from 103 to 7906, reaching a total of 15,204 participants. All included studies reported the ABO blood type of participants, and 10 included studies reported the treatment of participants and 4 studies [ 22 , 24 , 26 , 27 ] reported the data on Rhesus blood group system. The main study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on 4 studies [ 22 , 25 27 ] reported BC patients treated with RC and measured the blood type non-O (ref: O) on prognosis of included patients, the outcomes of pooled results did not demonstrate an influence of non-O blood group on disease recurrence-free survival (RFS), cancer-specific survival (CSS) and overall survival (OS) of the patients treated with RC for BC. What’s more, the blood type non-O has no association with an advanced pathologic tumor stage and lymph node metastasis in according to Engle’s study.…”
Section: Resultsmentioning
confidence: 99%
“…They found no significant difference in stage, lymph node status, histological subtype, disease-specific and overall survival rates. 14 The impact of blood group in muscle-invasive disease in patients receiving chemotherapy was also shown to be not helpful in prognosis. 15 Hence, further consideration of blood group in prognosis and risk assessment even in non-muscle disease is of questionable value.…”
Section: Discussionmentioning
confidence: 99%